JURNAL SISTEM PENDUKUNG KEPUTUSAN PENILAIAN EFEKTIVITAS PEMILIHAN DOSEN TERBAIK ITBA DIAN CIPTA CENDIKIA BANDAR LAMPUNG MENGGUNAKAN METODE AHP DAN TOPSIS: This study aims to select the best lecturer using the Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The criteria used in this research include teaching experience, research quality or academic contribution, involvement in academic activities, presentation quality or abilit - Pramodiyo Wilantara, Rangga; Wasilah, Wasilah; Triloka, Joko (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
The problem faced by ITBA Dian Cipta Cendikia is related to the assessment of the learning process which is currently still being carried out through filling out questionnaires by students and interviews. The assessment calculation process is still done manually, there needs to be a system that processes data on outstanding lecturers so that from this award all lecturers are motivated to develop their abilities.This research aims to select the best lecturer using the AHP and TOPSIS methods. The criteria used in this study include teaching experience, quality of research or academic contributions, involvement in academic activities, quality of presentation or ability to deliver material, openness to students, and the relevance of the material to the course. The weights for each of the seven criteria were determined through AHP, while TOPSIS was used to determine the best lecturer based on relative preference values. The results of the study indicate that Akni Widyastuti has the highest relative preference value, namely 0.700. The calculations carried out show that the AHP and TOPSIS methods provide structured and objective results in determining the best lecturers based on various relevant criteria. Â  Keywords: Analytic Hierarchy Process (AHP), TOPSIS, Decision Support System.